Obese people less likely to consider their next meal when considering portion sizes. (Research'eu results magazine)
Part-supported through the EU-funded NUDGE-IT (The Neurobiology of Decision-Making in Eating-Innovative Tools) project, researchers have undertaken a detailed study which shows how obese people are able to crucially discount future meal times.